Nasopharyngeal colonization at birth and the development of early-onset neonatal sepsis - Andi Dwi Bahagia Febriani; Nilam Sartika Putri; Ema Alasiry; Dasril Daud (Indonesian Pediatric Society, 2020)
Background Neonatal sepsis is one of the major causes of morbidity and mortality in neonates. Exposure to maternal bacteria during pregnancy or delivery allows for colonization of the normal upper airway. Such bacteria become the major ecological species in the infant. If the colonizing bacteria invade the bloodstream, early-onset neonatal sepsis (EONS) could occur. Objective To evaluate for an association between colonization of the newborn nasopharynx and EONS, as well as for agreement between nasopharyngeal swab culture and blood culture isolate results. Methods This prospective cohort study was conducted in Dr. Wahidin Sudirohusodo General Hospital and Ibnu Sina Hospital, Makassar, South Sulawesi. Nasopharyngeal swab culture was taken within 2 hours of life from newborns who met the inclusion criteria, then they were followed up for signs of EONS. Blood culture was taken from subject with EONS. Results Of the 100 newborns, 69 (69%) had nasopharyngeal bacterial colonization, of whom 5.8% (4/69) experienced EONS. Of the remaining 31 (31%) without colonization, 9.7% (3/31) experienced EONS. There was no significant difference in frequency of EONS between newborns with and without nasopharyngeal colonization. Although Gram-negative bacteria were predominant among colonized newborns, there was no significant difference to numbers of Gram-positive bacteria as a causative agent of EONS. Only one patient with EONS had the same bacterial species in both the nasopharynx and blood culture isolate. Conclusion Newborn nasopharyngeal colonization at birth is not associated with EONS.